2011
DOI: 10.1007/s00103-011-1270-9
|View full text |Cite
|
Sign up to set email alerts
|

Motivierende Gesprächsführung in der Adipositas-Therapie von Jugendlichen

Abstract: Group and individual counseling sessions play a key role in adolescent obesity treatment. The requirements of these training sessions are defined in national guidelines, e.g., the German "Adipositas-Konsensuspapier" (Obesity Consensus Paper). Literature research between 2005 and 2010 showed that the long-term effects of these sessions were low, based on five reviews considering obesity treatment and six reviews dealing with motivational interviewing (MI). The reviews underline high attrition and dropout rates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
0
5
0
2
Order By: Relevance
“…Of the single tools used, only the family approach has evidence of efficacy [13,15,46]; other tools have been evaluated in single studies. Motivational interviewing, introduced in therapeutic guidelines and recommendations in many countries, has not proven to be effective [18,[47][48][49][50][51]. The reduction of a sense of guilt is proposed by the authors of this study, but poorly sustained by others.…”
Section: Family Therapeutic Educationmentioning
confidence: 77%
“…Of the single tools used, only the family approach has evidence of efficacy [13,15,46]; other tools have been evaluated in single studies. Motivational interviewing, introduced in therapeutic guidelines and recommendations in many countries, has not proven to be effective [18,[47][48][49][50][51]. The reduction of a sense of guilt is proposed by the authors of this study, but poorly sustained by others.…”
Section: Family Therapeutic Educationmentioning
confidence: 77%
“…In einer Pilotstudie erwies sich ein Schulungsprogramm mit unterschiedlichen Modulen für Intender und Actor, das im Rahmen des Projektes MoReMo entwickelt wurde, als machbar und erste Hinweise auf die Wirksamkeit konnten gewonnen werden [30]. Hierbei war in Übereinstimmung mit früheren Studien insgesamt die Methodik der Motivierenden Gesprächsführung sehr geeignet, um die Jugendlichen je nach Motivationsstadium in ihrer Intention, Handlungs- und Bewältigungsplanung zu unterstützen und deren Selbstwirksamkeitserwartungen aufzubauen [31,32]. Übereinstimmend mit früheren Befunden (vgl.…”
Section: Fazit Für Die Klinische Praxisunclassified
“…MI is a clientcentered conversation technique and a directive approach to explore ambivalence and develop intrinsic motivation purposefully. Building on a patient empowerment perspective, MI has emerged as an effective counseling technique to detect comorbid mental health problems and support health-related lifestyle changes [10][11][12][13][14]. In MI conversations, various techniques are used, such as open-ended questions, active listening, providing con rmation, summarizing, a rming, and re ecting on behaviour [7,9].…”
Section: Introductionmentioning
confidence: 99%
“…health behaviour and health service use) in the meantime. Furthermore, it was shown that MI improves the utilization of psychiatric care services by young patients [12,[15][16][17][18][19][20]. Published data suggests implementing MI techniques into clinical practice to be feasible, as even 15-minute counseling applying MI techniques can be effective [14].…”
Section: Introductionmentioning
confidence: 99%